The Evolution and Culture of Digital Contemporary Photography : A Literature Review: A Literature Review - Siri, Hishamuddin; Khairani , Mohd Zahuri (Advances in Humanities and Contemporary Studies, 2022)
Today's development is more faced with patterns and tendencies to be more subjective, experimental, emotional, interpretive, and even capable of determining the character. Similarly, in general, digital photography shows the angle of the expansion of democracy to photography today. Nevertheless, after the industrial revolution, there was a change in the meaning of art that triggered photography's art. In the meantime, the appearance of this exciting work is livelier and more widespread through social media sites and is known by the nickname "Fear of Missing Out (FOMO). Today's development and culture are the primary sources of current sharing when these mobile phone pictures become part of the critical image. Simultaneously, the objects through the angle of photographic change, especially the development of currents and the conventional transition to digital technology. Today's original and cultural definitions see from the cultural aspects that have an interrelationship between the direction of value by Kluchorn and Strodbeck and the measure in human problems by Inkeles.